A case report of hemosuccus pancreaticus: the cause of upper gastrointestinal bleeding demystified after 9 months of episodic bleeding - Marie Solange Mukanumviye; Dyna Nyampinga; Zainab Ingabire; Cedric Kwitonda; Felicien Shikama; Eric Rutaganda; Berhane Redae; Hanna Aberra; Marcellin Musabende; Peter Crook; Jean de Dieu Mbanzabugabo; Ferehiwot Bekele Getaneh; et al. (Frontiers in Gastroenterology, 2024)
Hemosuccus pancreaticus is a rare but potentially fatal cause of upper gastrointestinal (GI) bleeding. It is defined as bleeding from the pancreatic duct with blood draining into the duodenum through the ampulla of Vater. In patients with pancreatitis, peri-pancreatic blood vessels may be inflamed by pancreatic enzymes and form a pseudoaneurysm which can rupture and bleed into the pancreatic duct. We report a case of a 43-year-old man who presented with episodic upper GI bleeding of unclear etiology over 9 months without a clear documented history of pancreatitis. The etiology remained elusive even after multiple upper and lower endoscopies. Computed tomography angiography of the abdomen and pelvis during an acute episode detected a pseudoaneurysm of the gastroduodenal artery (GDA) with contrast extravasation into the dilated pancreatic duct. The pseudoaneurysm was treated with coil embolization, resulting in a persisting resolution of the patient’s symptoms. Clinicians should consider abdominal angiography when diagnosing obscure GI bleeding.